Ridge-axis and Off-axis volcanic massive sulphide, Cyprus-type, in the Mawat Ophiolites, Kurdistan-Iraq, Reconnaissance survey - Palinkas, Ladislav A.; Mirza, Tola A. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Zagros orogenic belt is a part of the a-Himalayan orogenic system which streatches in continuity between the Turkish Taurus and the Iranian Zagros ophiolites, complementary with those in Balkans in Europe and to Pakistan and Tibet in Asia. Tectonic analysis of the Mawat ophiolit complex registered system of rupture elements of variable intensity and strike directions, marking the thrust-fault boundaries of the Mawat ophiolite complex. The first order E-W elements delineate the boundaries among three major tectono-stratigraphic units: i) Northern Mawat Group (NMG), (ii) Median Intrusive complex (MIC), (iii) Southern Waraz Group (SWG). SWG has fully developed sheeted dyke complex, while its existence in the NMG and MIC is ambiguous. In addition, NMG and MIC have significantly different mélange units. Sulphide mineralization in the Mawat ophiolite is a part of the sub-sea floor alteration process. The mineralization events in the Waraz meta-basalts are diachronous and not formed from the single fluid and under the same P/T conditions. Its polyphase character could be constrained, at least, into two major episodes: 1) The low temperature hydrothermal (LTH) and 2) The high temperature hydrothermal episode (HTH). They differ by contrasting alteration assemblages. The HTH is related to intrusion of plagiogranites which play active role in the ore forming process. It implies a new regional magmatic impulse as a source of heat and energy for hydrothermal circulation. While the low temperature episode (LTH) is related to magmatism along the ridge-axis, HTH is an off-axis event. The major VMS deposit prospects and Cu-ore showings are situated within the „Shear Zone“, gently arcuated tecto-magmatic belt trending NW-SE, along the western side of the Median Intrusive complex from Mawat village toward the Waraz area. It encountered basic and acidic intrusions, diorites, quartz dolerites and plagiogranites, with pervasive epidotisation, as a dominant alteration process. Extrusive rocks in the Northern Mawat Group bear elements of boninitic magmatism. The Shear Zone ore occurences are parallel with the possible palaeo-spreading ridge-axis, but coincide with a newly established off-axis ridge, displaced temporally and spatially during supra-subduction initiation.
Keywords: VMS; Cyprus-type; supra-subduction ophiolites; plagiogranites; boninites; mélanges; Mawat ophiolites; Kurdistan-Iraq